2002
DOI: 10.1590/s1519-566x2002000100024
|View full text |Cite
|
Sign up to set email alerts
|

Natural enemies of the chinch bug, Blissus antillus Leonard (Hemiptera: Lygaeidae: Blissinae), pasture pest in Rio de Janeiro state, Brazil

Abstract: Neotropical Entomology 31(1): 165-167 (2002) Inimigos Naturais do Percevejo das Gramíneas, Blissus antillus Leonard (Hemiptera:Lygaeidae: Blissinae), Praga (Hymenoptera: Scelionidae), was observed on only two occasions attacking eggs which had been collected on plant stems in the field. These natural enemies are possible candidates for biological control programs. Despite extensive sampling, B. antillus was not observed to be infected by entomopathogenic fungi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Townsend et al (2006) found values of mite parasitism up to 20.3% for Leptus mites having Leiobunum formosum (Opiliones: Sclerosomatidae) as hosts in southeastern Virginia in above ground habitats. Parasitism of this erythaeid mite varied from 2.4 to 4.3 in the chinch bug, Blissus antillus Leonard (Hemiptera: Lygaeidae), in pastures in Rio de Janeiro state, Brazil (Coracini and Samuels, 2002) and 0.51% of parasitism was observed by Miranda and Bermúdez (2008) in calliphorid flies by Macrochelidae, Erythraeidae and Histiostomatidae mites in Panamá. Townsend et al (2008) showed a prevalence of infestation of 9.9% of this mite group parasitizing harvestmen from the Cranaidae and Manaosbiidae families.…”
Section: Discussionmentioning
confidence: 97%
“…Townsend et al (2006) found values of mite parasitism up to 20.3% for Leptus mites having Leiobunum formosum (Opiliones: Sclerosomatidae) as hosts in southeastern Virginia in above ground habitats. Parasitism of this erythaeid mite varied from 2.4 to 4.3 in the chinch bug, Blissus antillus Leonard (Hemiptera: Lygaeidae), in pastures in Rio de Janeiro state, Brazil (Coracini and Samuels, 2002) and 0.51% of parasitism was observed by Miranda and Bermúdez (2008) in calliphorid flies by Macrochelidae, Erythraeidae and Histiostomatidae mites in Panamá. Townsend et al (2008) showed a prevalence of infestation of 9.9% of this mite group parasitizing harvestmen from the Cranaidae and Manaosbiidae families.…”
Section: Discussionmentioning
confidence: 97%
“…Life cycle includes seven parasitic larval stages and free living nymphs and adults (SoutHcott 1992). Leptus larvae are ectoparasites of a wide range of arthropods: arachnids (Acari, Araneae, Opiliones, Pseudoscorpiones, Scorpiones) (Baker & Selden 1997), Mecoptera (Seeman & Palmer 2011), Heteroptera (Pereira et al 2012;coracini & SamuelS 2002), social insects (FletcHtmann 1980;teixeira 2011) (vieira et al 2011). In Brazil, Leptus was reported parasitizing predatory and phytophagous bugs in Minas Gerais (Pereira et al 2012), honeybees in São Paulo (teixeira 2011), and Sarcophaga fly Tricharaea (Sarothromyia) femoralis (Schiner) (Diptera: Sarcophagidae) in Itaipu beach, Maricá, Rio de Janeiro (Pinto et al 2014).…”
mentioning
confidence: 99%